Regulating forestry: experience with compliance and enforcement over the 25 years of Tasmania's forest practices system - Wilkinson, G.R; Schofield, M; Kanowski, P. (Elsevier, 2014)
Tasmania's forest practices system, one of the most prescriptive globally and the most comprehensive in Australia, has evolved over the last 25 years in response to public demands for high standards of governance, accountability and transparency of forest regulation on both public and private lands.The system was developed in the context of strong contestation, in Tasmanian and Australian civil society and politics, about appropriate forest policies and practices in Tasmania.The system is governed by a Forest Practices Act, which provides for a co-regulatory approach administered by an independent statutory body, the Forest Practices Authority.All forest operations must be undertaken in accordance with a certified forest practices plan, prepared and certified by accredited Forest Practices Officers employed by forest managers.These co-regulatory components of the system are supported by independent monitoring and enforcement by the Forest Practices Authority.This paper describes the genesis and evolution of the Tasmanian forest practices system, and summarises the range of measures employed to foster high levels of compliance, with an emphasis on training and education, self-monitoring and reporting by the industry, independent monitoring by the Forest Practices Authority, and corrective actions, backed by enforcement provisions.Compliance monitoring over 27 years demonstrates rapid improvement in the decade following establishment of the system, with consistently high levels of achievement subsequently.However, larger corporate forest managers consistently achieve higher rates of compliance than do small-scale forest owners, and redressing this imbalance has been a recurrent theme in Tasmania's forest practices system.Experience of implementation of Tasmania's forest practices system suggests that well-designed and implemented co-regulatory approaches, with high levels of transparency, can be effective in delivery of good technical standards of forest practices and high levels of compliance.However, these will not in themselves mitigate public concern about forest management practices unless the policies governing those practices have broad support in civil society.